Efektivitas Intervensi Psikoedukasi dan Dukungan Psikososial terhadap Beban Perawat Keluarga Pasien Penyakit Ginjal Kronik - Asiandi Asiandi; Irmalita Wigati; Asrin Asrin (JURNAL KEPERAWATAN MERSI, 2026)
Background: Chronic kidney disease (CKD) is a growing global health problem that affects not only patients but also their families as primary caregivers. The caregiving burden often leads to psychological stress, anxiety, depression, and decreased quality of life. Objective: This study aims to analyze the effectiveness of psychoeducational and psychosocial support interventions in reducing caregiver burden and psychological distress among families of CKD patients in community health centers (Puskesmas) in Banyumas Regency. Methods: The study used a randomized controlled trial with two parallel groups (intervention and control) was conducted. A total of 100 caregivers were recruited from four Puskesmas using randomized allocation. The intervention group received an 8-week structured family-based psychoeducation program covering CKD education, treatment and diet management, stress management, coping strategies, family communication, social support, and problem-solving through lectures, group discussions, and counseling. The control group received routine health education without structured psychoeducational components. Data were collected using the Zarit Burden Interview (ZBI), Hospital Anxiety Depression Scale (HADS), Family APGAR, and SF-12 Quality of Life, and analyzed using Repeated Measures ANOVA. Results: The results showed a significant reduction in caregiver burden in the intervention group (p < 0.001). Furthermore, there was a decrease in anxiety and depression levels, as well as an increase in family functioning and quality of life for caregivers. Conclusion: The family psychoeducation intervention was effective in reducing caregiver burden and improving the psychological well-being of families of CKD patients. This intervention is recommended for integration into community nursing services at community health centers.